Epistemological Analysis of Differentiated Learning in Indonesian Subjects in The Independent Curriculum - Himmawati, Aulia (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Differentiated learning in an independent curriculum frees teachers to present learning according to the needs and potential of each student. However, differentiated learning in the independent curriculum is mostly analyzed from the point of view of pedagogy, while in this article will be discussed through epistemological analysis by describing how students acquire knowledge through a differentiated approach to Indonesian lessons in the independent curriculum. The type of research used is descriptive qualitative data collection techniques using literature studies or library research. The research data obtained from the journal sinta 6 to 2 amounted to 15 articles on the epistemology of differentiated learning in Indonesian subjects. This research instrument is the researcher himself (human instrument). Analytical techniques using epistemological analysis. The results obtained that differentiated learning helps students find, acquire, and understand knowledge in accordance with the character of students. The diversity of student character can be met at least by differentiating content, processes, products and learning environments so that differences in interests, learning readiness and learning profiles are met. Meanwhile, differentiation in Indonesian lessons seen from the content can be differences in reading themes, learning resources, and reading complexity. Differentiation in the process can be seen through the activities of students. Differentiation in products is seen from learning outcomes. Viewed from the learning environment, includes time and learning environment.